Gender and motivation for street racing in Malaysia - Nurullah, Abu Sadat; Makol-Abdul, Pute Rahimah; Abd Rahman, Saodah (Macrothink Institute, USA, 2012)
The purpose of this study was to identify social, economic, and psychological factors in street racing in Malaysia. The study also assessed gender differences in terms of the causes of participation in street racing, and the street racers’ personality in terms of spiritual well-being, self-efficacy, and self-esteem. A snowball sample of 122 street racers (males, n=99, Mean age=21.52, SD=4.25; females, n=23, Mean age=19.22, SD=2.47) responded to self-tailored questionnaires and existing scales. For female racers, ‘family violence’, ‘parental conflict’, and ‘parenting style’ were the major familial factors leading to street racing. In case of male racers, ‘parenting style’ and ‘relationship with family members’ were the main causes of street racing. A sizeable percentage of male racers and female racers identified ‘social contact with the street racers’, ‘learned attitudes which encourage street racing’, ‘mass media and peer influences’ as causes of street racing. Both groups of respondents cited ‘social pressure’, ‘social labelling’, ‘social isolation’, ‘opportunities for joining street racing’, ‘limited surveillance of authority’, and ‘limited recreational and sports facilities’ as reasons for involvement in street racing. In terms of psychological factors, considerable percentage of male racers and female racers reported ‘self-image’, ‘desire for recognition and attention’, ‘escape from social-psychological stress’, and ‘self-actualisation’ as important factors leading to street racing. Unemployment was found to be one important reason for street racing almost equally by both the groups. Significant differences in mean spiritual well-being and self-efficacy scores of male racers and female racers did not exist. However, male racers obtained significantly higher mean self-esteem score than female racers.